2021
DOI: 10.1002/ange.202112907
|View full text |Cite
|
Sign up to set email alerts
|

Zr(OH)4‐Catalyzed Controllable Selective Oxidation of Anilines to Azoxybenzenes, Azobenzenes and Nitrosobenzenes

Abstract: The selective oxidation of aniline to metastable and valuable azoxybenzene,a zobenzene or nitrosobenzene has important practical significance in organic synthesis.However, uncontrollable selectivity and laborious synthesis of the expensive required catalysts severely hinders the uptake of these reactions in industrial settings.Herein, we have pioneered the discovery of Zr(OH) 4 as an efficient heterogeneous catalyst capable of the selective oxidation of aniline,u sing either peroxideo rO 2 as oxidant, to selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…As a proof-of-concept application, oxidative coupling of anilines to azo aromatic compounds was used as the probe reaction (Fig. 4a ) 39 41 . Hollow mesoporous h-CoNC was tested compared with the counterparts of hollow NC (h-NC), hollow NC with Co nanoparticles (h-Co NP NC), and solid CoNC (s-CoNC), which were derived from hollow ZIF-8, hollow ZnCo-BZIF with Zn/Co ratio of 20:1, and solid ZnCo-BZIF with Zn/Co ratio of 60:1, respectively (see SI Methods and Supplementary Figs.…”
Section: Resultsmentioning
confidence: 99%
“…As a proof-of-concept application, oxidative coupling of anilines to azo aromatic compounds was used as the probe reaction (Fig. 4a ) 39 41 . Hollow mesoporous h-CoNC was tested compared with the counterparts of hollow NC (h-NC), hollow NC with Co nanoparticles (h-Co NP NC), and solid CoNC (s-CoNC), which were derived from hollow ZIF-8, hollow ZnCo-BZIF with Zn/Co ratio of 20:1, and solid ZnCo-BZIF with Zn/Co ratio of 60:1, respectively (see SI Methods and Supplementary Figs.…”
Section: Resultsmentioning
confidence: 99%
“…[42][43][44][45] It consists of bridging hydroxyl (b-OH) and terminal hydroxyl (t-OH) groups. 46,47 Research has indicated that these sites serve as Brønsted acidic sites and Brønsted basic sites, respectively. 48,49 Therefore, these unique multi-types of Zr-OH sites provide the possibility to solve the above claims for the selective reaction of alcohols using the same catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, there is a growing fascination with creating more environmentally friendly processes, particularly by employing heterogeneous catalysts due to ease of separation, without causing a problem of waste disposal, and the option of reuse of heterogeneous catalysts instead of homogeneous ones. 25–27 In the last few decades, nanoparticles as catalysts have garnered considerable interest because of their enhanced selectivity and strong catalytic activity in organic reactions. 28–30 Recently, a variety of new nano-catalysts, designed specifically for the transamidation of amides, have been developed, such as Fe(OH) 3 @Fe 3 O 4 nanoparticles, 31 guanidine acetic acid (GAA) nanoparticles, 32 magnetically separable Fe 3 O 4 nanoparticles, 33 mesoporous silica nanoparticles (MSNs), 34 a sulfated poly borate nanocatalyst, 35 an Fe 3 O 4 –OSO 3 H nanocatalyst, 36 a SiO 2 –CeO 2 hybrid nanocomposite, 37 and nanosized zeolite beta (MSNs) 38 are used for primary amides and citric acid-coated nanoparticles (Fe 3 O 4 –CA NPs) for transamidation of primary and secondary amides.…”
Section: Introductionmentioning
confidence: 99%